Stability and structural evolution of double-stranded DNA molecules under high pressures: A molecular dynamics study - Herrera-Velarde, Salvador; Villanueva-Valencia, José Ramón; Mendoza-Espinosa, Paola; Castañeda-Priego, Ramón (Frontiers in Physics, 2023)
Conformational changes and stability of interacting double-stranded DNA chains under high hydrostatic pressure in biological systems are striking topics of importance to study several biomolecular phenomena: To unravel the physiological conditions at which life might occur and to ensure the right functionality of the biochemical processes into the cell under extreme thermodynamic conditions. Such processes could shed light on the physicochemical properties of the DNA under high confinenment and how a virus releases its genome in order to infect a cell and to promote the process of viral replication. To achieve a few steps toward this direction, we propose an all-atomistic molecular dynamics approach in the NPT ensemble to account for how the interplay of DNA - DNA interaction, hydrogen bonding, and the hydrostatic pressure modifies both the DNA conformational degrees of freedom and the spatial organization of the DNA chains in the available volume. We consider two interacting double-stranded DNA chains immersed in an explicit aqueous solution. Our preliminary results highlight the role of hydrogen bonding and electrostatic interactions between DNA strands to avoid denaturation and to provide mechanical stability for the DNA. The structural evolution, whose kinetics depends on the relaxation of the stresses induced by the pressure, indicates that almost in all pressure conditions, the equilibrium configuration corresponds to an alignment of the two double-stranded DNA molecules along their main axis of symmetry; the rearrangement between the two approaching DNA dodecamers does not always correspond to complementary base pairs and becomes a function of the thermodynamic conditions.